Artemis Fowl [compact disc, unabridged] The eternity code - Colfer, Eoin (Colfer, Eoin. Artemis Fowl, 2004)
After Artemis uses stolen fairy technology to create a powerful microcomputer and it is snatched by a dangerous American businessman, Artemis, Juliet, Mulch, and the fairies join forces to try to retrieve it.